(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2009)
The article presents one of ways of stylistic syntacs – rhetorical question. The function of rhetorical questions is examined on the material of properly information and comment types of information style. The expressive-functional potential of rhetorical questions is also presented there.